Increased Activity, Motivation and Learning Outcomes Mathematics with Learning Model Cooperative Type Numbered Head Together in Grade III Students - Samsul Adianto (IJECA (International Journal of Education and Curriculum Application), 2018)
The research seeks to examine how models of the cooperative learning of type Number Head Together are able to improve student activity, motivation and learning outcomes. The purpose of this study type is the research action Class (PTK), the data source in this research is all grade III students at SDN Sungai Kunjang. The data collection techniques are observations, tests, and documentation. The data analysis technique used is a descriptive quantitative analysis technique and qualitative analysis. The results of the study and discussion showed (1) cooperative learning Model type Numbered Heads Together (NHT) can increase the learning activity of class III elementary School of SD State 003 Samarinda. It is shot from the average cycle activity I reached 2.91 and increased by 3.16 in cycle II; (2) The Model of cooperative learning type Numbered Heads Together (NHT) can increase the motivation to learn to study students of grade III SD Negeri 003 Kunjang River. Increased motivational learning is gained from the observation results of each cycle, where cycle I reaches 3.3, and cycle II reaches 3.64; (3) The Model of cooperative learning type Numbered Heads Together (NHT) can improve student learning outcomes of Grade III Elementary School, 003 Sungai Kunjang. This is an image of the learning value of the cycle I reached at 83.33%, and cycle II reaches 95.83%.